After shock : learning to reinhabit my body after illness - Awdish, Rana (St. Martin's Press, 2026)
In the aftermath of her own critical illness, physician and writer Dr. Rana Awdish finds herself oddly estranged her from her own body. Medicine has conditioned her to view sick bodies as broken objects, not as sites of meaning, mystery, and quiet wisdom. So, when her own body warns her that she'll be dead in five years, she's unsure whether to trust it enough to follow where it leads. Allowing for this kind of innate, bodily wisdom would require her to dismantle and reconfigure her entire belief system. She decides to take a leap of faith, abandon certainty and surrender to the message-a choice that ultimately saves her life. What emerges is a profound and vulnerable meditation on the true nature of healing. Guided by the evocative power of art from Frida Kahlo to Mark Rothko, as well as her own creative process, After Shock is part memoir and part guidebook to sustaining wonder and attention to beauty even in the face of grief and loss. Awdish elegantly draws us into a space where our perception shifts and curiosity leads to profound revelation. She invites us to reclaim the power that resides in our attention, relationships and willingness to stay present with suffering long enough for it to transform into something else. Through her poetic prose and evocative imagery, we learn to see differently, feel deeply, and trust that healing is always possible.